Diversity of Secondary Metabolites of Eurycoma Longifolia and Its Prospects as Anticancer Agents Based on Sumatran Bioresources: A review - Budi Mansyah (Universitas PGRI Palembang, 2025)
Eurycoma longifolia, commonly known as Tongkat Ali or Pasak Bumi, is a traditional medicinal plant widely used in Southeast Asia, including Sumatra, Indonesia. It is traditionally recognized for its aphrodisiac and general health-promoting properties. However, recent phytochemical and pharmacological studies have identified a diverse range of secondary metabolites in this plant, such as quassinoids, alkaloids, triterpenes, and squalene derivatives, that exhibit promising anticancer activities. This review aims to comprehensively explore the diversity of secondary metabolites found in E. longifolia populations in Sumatra and assess their potential as anticancer agents by analyzing local bioresources. A systematic literature review was conducted by collecting data from scientific databases including PubMed, ScienceDirect, and Google Scholar using targeted keywords. Selection criteria focused on studies discussing secondary metabolite content, anticancer mechanisms, toxicological data, and drug development potential. The findings show that several compounds in E. longifolia can inhibit cancer cell proliferation, induce apoptosis, and prevent angiogenesis and metastasis in vitro and in vivo. Despite challenges such as low bioavailability and lack of clinical trials, the plant’s abundant presence in Sumatra and the bioactivity of its metabolites make it a promising candidate for the development of novel, plant-based anticancer therapies. Further research and standardization are recommended to optimize its pharmaceutical application.